2018
DOI: 10.1111/jdv.15012
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in patients with moderate‐to‐severe psoriasis and comparison of change from baseline after treatment with guselkumab vs. adalimumab: results from the Phase 3 VOYAGE 2 study

Abstract: Guselkumab treatment was associated with greater improvements in symptoms of anxiety and depression scores in patients with psoriasis compared with placebo and adalimumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 43 publications
4
69
1
Order By: Relevance
“…The HADS‐A and HADS‐D scores were also higher than previously reported in other chronic skin disorders, e.g. patients enrolled in clinical trials of biologics for moderate‐to‐severe psoriasis (6·8–7·2 and 5·3–5·7, respectively), and other medical disorders such as diabetes (5·7 and 5·0, respectively) and HIV (6·5 and 5·5, respectively) . A cross‐sectional study that used HADS scores of 1519 adults with AD from six U.S. medical centres found that approximately one‐quarter of patients with mild AD and one‐half of patients with moderate‐to‐severe AD had symptoms of anxiety or depression, with even more severe HADS scores among those with uncontrolled AD .…”
Section: Discussionmentioning
confidence: 90%
“…The HADS‐A and HADS‐D scores were also higher than previously reported in other chronic skin disorders, e.g. patients enrolled in clinical trials of biologics for moderate‐to‐severe psoriasis (6·8–7·2 and 5·3–5·7, respectively), and other medical disorders such as diabetes (5·7 and 5·0, respectively) and HIV (6·5 and 5·5, respectively) . A cross‐sectional study that used HADS scores of 1519 adults with AD from six U.S. medical centres found that approximately one‐quarter of patients with mild AD and one‐half of patients with moderate‐to‐severe AD had symptoms of anxiety or depression, with even more severe HADS scores among those with uncontrolled AD .…”
Section: Discussionmentioning
confidence: 90%
“…For example, Breuer et al [21] found that psoriasis patients with more symptoms of depression at baseline showed less PASI reduction at discharge after a 3-week multidisciplinary inpatient rehabilitation program. In addition, Gordon et al [20] demonstrated that reductions in depression and anxiety scores were correlated with PASI score improvement in psoriasis patients receiving 24-week guselkumab or adalimumab treatment; however, the predictive values of depression and anxiety before treatment for clinical response to TNF-α inhibitors were not investigated in their study. In our study, we found that PASI 75/90 response rates in depressed patients were lower compared with those in non-depressed patients at M6, and depression symptoms at baseline was an independent predictive factor for the lower possibility of PASI 75/90 response achievement after etanercept treatment in psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial problems are not only associated with poor skin conditions but also have negative impacts on prognosis in psoriasis patients with various treatments [11, 20-22]. For example, Breuer et al [21] found that psoriasis patients with more symptoms of depression at baseline showed less PASI reduction at discharge after a 3-week multidisciplinary inpatient rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
“…A single suicide attempt was reported in a patient taking adalimumab in VOYAGE 1 . In VOYAGE 2, greater improvements in anxiety and depression scores were seen in patients treated with guselkumab than in those who received adalimumab or placebo …”
Section: Safety Data From Clinical Trialsmentioning
confidence: 99%
“…41 In VOYAGE 2, greater improvements in anxiety and depression scores were seen in patients treated with guselkumab than in those who received adalimumab or placebo. 46 The NAVIGATE trial assessed guselkumab in adult patients with an inadequate response to ustekinumab. 43 All patients (n = 871) initially received open-label ustekinumab (45 or 90 mg at Weeks 0 and 4).…”
Section: Guselkumabmentioning
confidence: 99%